Atividade biológica do isoeugenol e acetaminas híbridos frente a leveduras do gênero Candida - Medeiros, Daianne de Sousa (2018)
The oral cavity is an environment naturally inhabited by several species that microorganisms coexist without causing any harm to humans. Among fungal species, the Candida genus is the most frequently isolated in the oral cavity of healthy individuals, however, when there are changes of local or systemic factors in the host, these yeasts pass from the commensal state to the pathogen, triggering the infectious process called candidiasis. The present study aimed to evaluate the in vitro susceptibility of C. albicans and non-albicans strains (C. tropicalis and C. glabrata) against isoeugenol and nystatin by determining the Minimum Inhibitory Concentration (MIC); Minimum Fungicidal Concentration (CFM); interference on microbial micromorphology and product modulation test- checkerboard. In this study, 19 Candida strains were used, with 7 clinical isolates of C. tropicalis and one ATCC 13803 standard; four clinics of C. glabrata and its ATCC 90030 and five clinics and one standard (ATCC 76485) of C. albicans. Antifungal activity of isoeugenol can be observed in all isolates tested with MIC70% of 128 μg/mL. Hybrid acetamide molecules did not demonstrate any antifungal activity against the strains evaluated, with an MIC of 100% of 1024 μg/mL. The CFM/MIC ratio of isoeugenol indicated fungicidal activity in 84.21% of the strains tested. Isougenol was able to interfere in the formation of virulence structures in C. albicans and C. tropicalis species at MIC, CIMX2 and CIMX4 concentrations. The modulation test of isoeugenol and nystatin demonstrated antagonist type interaction in C. glabrata LM-116, synergistic in C. tropicalis LM-211 and indifferent C. albicans LM-4b. From the data obtained in this study, it was possible to conclude that isoeugenol has good antifungal activity against the Candida species evaluated and may be a therapeutic alternative in the treatment of oral candidiasis.